Differences in geographical distribution of soil chemical properties of agricultural lands in Penjwen district using Gis - اليق, طالب الدكتوراه سروار عبد الله محمد اليق محمد; صابر, آ.د.سايا سليم صابر (Sulaimani Journal for Humanities, 2025)
The aim of this study is to present chemical properties for agricultural education and geographical distribution of these properties in Banjuin district "(North °45 45' 05"(Location of the astronomical location of Banjwen district between the latitude)°35 26'30"(W)°35 51'40, between the longitude) W )°46 20' 57"( East, and with an area of propagation )1138.56 km2 For the purposes of the reservoir, determine the chemical properties of the environment under the influence of the natural environment of the area, such as the geological formations that have a large influence On the characteristics of moisture in the region, limestone which is the main source of calcium carbonate, and the minerals it contains The results of the study show that agricultural production in the region is appropriate for the country Agricultural income, especially intellectual income, with some secondary problems related to the methods and quality of education I use Before the farmers themselves
Keywords: Soil; chemical properties; solar species; geographical distribution by application Gis